2022
DOI: 10.1111/ajd.13958
|View full text |Cite
|
Sign up to set email alerts
|

Toxic epidermal necrolysis and Stevens‐Johnson syndrome after COVID‐19 infection and vaccination

Abstract: Stevens‐Johnson Syndrome (SJS) is a rare but severe skin reaction characterized by blistering and peeling of the skin and ulcerations of mucous membranes; toxic epidermal necrolysis (TEN) is a subset of SJS characterized by the involvement of >30% of the skin. Though previously associated with drugs and infections, discussions on the association between TEN/SJS and COVID‐19 have been limited. We present a review of TEN/SJS after COVID‐19 infection and vaccination. Literature searches were conducted on PubMed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…Only case reports and small sample-size case series are available in the literature on the association between infection and SJS/TEN. Mycoplasma pneumoniae , coxsackievirus A6 and COVID-19 have been reported to cause SJS/TEN [ 22 , 23 ]. A microbiological study reported that higher germ counts of Pseudomonas spp., Streptococcus ssp., Acinetobacter ssp.…”
Section: Aetiologymentioning
confidence: 99%
“…Only case reports and small sample-size case series are available in the literature on the association between infection and SJS/TEN. Mycoplasma pneumoniae , coxsackievirus A6 and COVID-19 have been reported to cause SJS/TEN [ 22 , 23 ]. A microbiological study reported that higher germ counts of Pseudomonas spp., Streptococcus ssp., Acinetobacter ssp.…”
Section: Aetiologymentioning
confidence: 99%
“…Most of these reactions are self‐limiting and can be managed in primary care with emollients, antihistamines and topical corticosteroids, if required. Although less common, cutaneous reactions following vaccination that require secondary care input include inflammatory conditions such as eczema and psoriasis, neutrophilic dermatoses, and autoimmune disorders ( eg cutaneous lupus erythematous, 14‐16 alopecia areata, 16‐18 autoimmune bullous disorders and severe cutaneous adverse reactions [SCARs]) 19 …”
Section: Cutaneous Adverse Reactionsmentioning
confidence: 99%
“…SCARs secondary to COVID‐19 vaccination are increasingly recognised in case reports and case series 19,29‐31 . SCARs include AGEP, drug reaction with eosinophilia and systemic symptoms (DRESS), SJS and toxic epidermal necrolysis (TEN).…”
Section: Cutaneous Adverse Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Drugs especially antimicrobials, antipyretic analgesics and sulfa drugs are the primary cause of SJS/TEN, but Mycoplasma or viral infections can also be triggers [1]. In recent years, there have been reports of SJS/TEN due to immune checkpoint inhibitors (ICIs) [2] and coronavirus disease 2019 (COVID-19) vaccination or infection [3]. Clinically, severity is distinguished based on the amount of skin detachment: SJS < 10%, SJS/TEN overlap of 10-30%, and TEN > 30% [4].…”
Section: Introductionmentioning
confidence: 99%